Addition of plant extracts to meat and meat products to extend shelf-life and health-promoting attributes: an overview. (February 2020) - Munekata, Paulo Eduardo S; Rocchetti, Gabriele; Pateiro, Mirian; Lucini, Luigi; Domínguez, Rubén; Lorenzo, Jose Manuel
Highlights: Plant extracts are interesting food ingredients to improve meat and meat products. Guarana seed, pitanga leaf and black pepper are important sources of antioxidants. Drumstick flower enhance the antioxidant and fiber content in meat products. Sage processing by-product is a natural and sustainable source of antioxidants. Abstract : The use of plant extracts as source of bioactive compounds is becoming an appealing strategy to increase quality and health-related characteristics of fresh meat and meat products. Indeed, considering their natural origins, bioactive compounds obtained from plant (such as black pepper, oregano, guarana seeds and drumstick flowers) are ideal candidates to replace synthetic antioxidants (generally considered less safe) to increase the shelf life of meat products. At the same time, these plant extracts can ameliorate, either directly or indirectly, the functional value of meat products. On these bases, taking into account the more recent optimization of different extraction methods to formulate ad-hoc green antioxidant extracts, this mini-review aims to highlight the different applications of plant extracts as source of bioactive compounds able to improve shelf-life and functional properties of meat and meat products.